Language planning and development aid: the (in)visibility of language in development aid discourse. Issue 4 (2nd October 2017) - Taylor-Leech, Kerry; Benson, Carol
ABSTRACT: Despite the essential role of local, regional, national and international languages in human development, there is little reference to language planning in development aid discourse. Beginning with definitions of development aid and language planning, the paper examines how the two were linked in pre- and post-colonial times, showing how language planning scholarship has responded to the overarching shifts in understandings of development over time. While we find that language planning maintains a low profile in human development documents, we note some positive signs in UNESCO's and UNICEF's continuing support for language issues. We contrast this support with the World Bank's concern with measurable outcomes. We conclude with an analysis of how the contributions to this special issue exemplify some of the tensions inherent in language planning for development in a global age.